Testing a measurement model of multidimensional intrinsic motivation in studying for examination - Syed Mustafa, Syarifah Muzlia; Elias, Habibah; Mohd Noah, Sidek; Roslan, Samsilah (Universiti Putra Malaysia Press, 2012)
Intrinsic motivation is seen as a stronger driver for academic success compared to extrinsic motivation. This study proposed a comprehensive framework for intrinsic motivation by incorporating five different theories in a measurement model. The reason is that there is no single theory that can explain the internal drive to study since different motives logically work together to create the intrinsic motivation. The purpose of this study was to test a measurement model that combined five different theories of motivation when students studied for their examination. The five intrinsic forces were future time perspective, achievement need, learning goal orientation, expectation values, and self determination. The items for each construct were constructed based on literature review in order to provide a tool to measure the level of intrinsic motivation for studying examinations in high school students. Using confirmatory factor analysis, the five–dimension model of intrinsic motivation was found to be acceptable. However, due to high correlations among the five constructs, a second-order factor model measuring intrinsic motivation was suggested. Although the items were found to have acceptable reliability and validity, there is a need to further test the models with different and larger samples. Results have practical implications for teachers to utilize the instrument as well as to pay more attention to the importance of cultivating intrinsic motivation in school children.